Short Note: Well Rounded Kuta and Tanjung Aan Lombok Beach Sand - Koesoemadinata, R.P.; van Gorsel, J.T.; Darman, Herman (Berita Sedimentologi, 2012)
Coarse, well rounded carbonate sand grains are found in Kuta and Tanjung Aan beach Lombok. These kinds of sands are also common on Sanur Beach and other localities along the East coast of Bali, where many visitors believed them to be ooids (oolites). The grains are generally about 3-4 mm in diameter and well rounded. The colors of the grains are white to light-brownish white. In places they are mixed with coral remain and other small shells which are angular to sub-angular or sub-rounded to oval shape, with generally the same grain size or larger.